Aspek Etika dan Konflik Sosial dalam Novel Lelaki Harimau Karya Eka Kurniawan (Tinjauan Sosiologi Sastra) - Ali Murtadoh; Dwi Setiyadi; Panji Kuncoro Hadi (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
Study this aim for describe and explain Ethics and conflict social in novelManTiger work Eka Kurniawan. kindly whole, purpose study this is for gather data and analyze aspect ethics and conflict social in novelManTiger work Eka Kurniawan. kindly special,fordescribe, analyze, interpret in a manner detail data which obtained, in study this, including study critics literature, specifically study sociology literature, more prioritize description for get resultsfromstudy. Method study this is study qualitative, kind process study this produce data which characteristic descriptive form text or speech people which behavior could observed on aspect ethics which contained in novel Man Tiger work Eka Kurniawan, that is part ethics as not quite enough answer, obligation, and heart conscience. In construction conflict possibility appear fact which different between characteristics. Conflict the more strong until climax and there is the solution. Based on results analysis data, collected data about conflict moral and social in novel Man Tiger work Eka Kurniawan. Novel Man Tiger work Eka Kurniawan contain a number of aspect moral, that is aspect not quite enough answer, aspect obligation and aspect heart conscience. Aspect moral novel Man Tiger work Eka Kurniawan own three component, that is: (1) ethics not quite enough answer, (2) ethics obligation, and (3) ethics heart conscience. Aspect Ethics novel Man Tiger work Eka Kurniawan load 7 quote data moral about not quite enough answer, 8 quote data moral about obligation, and 15 quote data moral about heart conscience. In describe conflict social, in novel Man Tiger work Eka Kurniawan, author describe various conflict between figure in every situation. Besides that, researcher which analyze novel Man Tiger in conflict social find many very, that is there is 29 quote data.